The most elementary proof that ?. Issue 549 (17th October 2016) - Lord, Nick
Abstract : Here we present a simplification of one of the standard proofs that . We then look at extensions of the new approach, and add comments on the nature of the simplification (which relates to Step 1 below) and finally on the literature. As in most proofs of the result, we shall actually prove that ; because this is equivalent to the result sought.